2016
DOI: 10.1002/2016gl069191
|View full text |Cite
|
Sign up to set email alerts
|

Electron scale structures and magnetic reconnection signatures in the turbulent magnetosheath

Abstract: Collisionless space plasma turbulence can generate reconnecting thin current sheets as suggested by recent results of numerical magnetohydrodynamic simulations. The Magnetospheric Multiscale (MMS) mission provides the first serious opportunity to verify whether small ion‐electron‐scale reconnection, generated by turbulence, resembles the reconnection events frequently observed in the magnetotail or at the magnetopause. Here we investigate field and particle observations obtained by the MMS fleet in the turbule… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 50 publications
6
88
0
Order By: Relevance
“…Roberts et al, 2016;Perrone et al, 2016Perrone et al, , 2017. In addition, some results on very high-resolution data on electron scales have recently been provided by the Magnetospheric Multiscale (MMS) mission (Yordanova et al, 2016;Chasapis et al, 2017). Moreover, on the basis of kinetic simulations by Karimabadi et al (2014), one can suggest some interesting relationships of turbulent processes near shocks with reconnection processes.…”
Section: Magnetosheath Turbulencementioning
confidence: 99%
“…Roberts et al, 2016;Perrone et al, 2016Perrone et al, , 2017. In addition, some results on very high-resolution data on electron scales have recently been provided by the Magnetospheric Multiscale (MMS) mission (Yordanova et al, 2016;Chasapis et al, 2017). Moreover, on the basis of kinetic simulations by Karimabadi et al (2014), one can suggest some interesting relationships of turbulent processes near shocks with reconnection processes.…”
Section: Magnetosheath Turbulencementioning
confidence: 99%
“…Based on Cluster data, Retinò et al () observed many current sheets in the magnetosheath (shock downstream region) and reported reconnection. Yordanova et al () and Vörös et al () demonstrated signatures of ion and electron diffusion regions in magnetosheath current sheets observed by MMS. Based on MMS data, Phan et al () showed electron‐scale current sheets exhibiting reconnection in the magnetosheath, where only electron but no ion jets were detected, indicating that ions cannot respond to the small‐scale structures, and only electrons are involved in reconnection.…”
Section: Introductionmentioning
confidence: 95%
“…Elucidating the kinetic dynamics of thin current sheet equilibria is essential for understanding many fundamental plasma energization phenomena, such as the onset of magnetic reconnection, plasma turbulence, and wave instabilities (Harris, ; Priest, ; Daughton, ; Sundkvist et al, ). Detection of electron‐scale current sheets in Earth's magnetic environment has become possible with the high‐resolution instrumentation onboard the Magnetospheric Multiscale (MMS) spacecraft, which can resolve electron skin depth ( d e ) scale, filamentary currents narrower than the spacecraft separation (Phan et al, ; Phan et al, ; Yordanova et al, ; Wilder et al, ). Current sheets with thicknesses on the order of a few d e are often observed in association with the electron diffusion region (EDR) and separatrix regions of magnetic reconnection (Burch et al, ; Chen et al, ; Chen et al, ; Genestreti et al, ; Norgren et al, ; Torbert et al, ; Torbert et al, ; Wang et al, ; Webster et al, ).…”
Section: Introductionmentioning
confidence: 99%